Inclusive pedagogy in action: getting it right for every child. Issue 8 (3rd August 2018) - Florian, Lani; Beaton, Mhairi
ABSTRACT: A key assumption underpinning formative assessment strategies is that individual pupils must be fully involved in the process. While such engagement and attention on the individual is important, studies suggest that teachers do not always readily engage with formative assessment as a reciprocal process which involves pupils. Additionally, a focus on individual differences between pupils can be problematic if the work that is set for some is differentiated to such an extent that they are not able to participate in classroom activities with others. Inclusive pedagogy is an approach to teaching and learning that attends to individual differences between pupils but avoids the marginalisation that can occur when pedagogical responses are designed only with individual needs in mind. Using participant observation and video footage from three classrooms that captured 'learning moments' identified by teachers and pupils, this study documents how the professional craft knowledge of teachers develops as they learn to use what their pupils have to say about learning in the context of whole class teaching. By concentrating on the findings from one site, this paper shows how teachers can use what they learn from listening to pupils' self-assessments of their learning in ways that meet the standard of inclusive pedagogy.